2011
DOI: 10.1111/j.1751-553x.2011.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of hemoglobin point‐of‐care testing during major pediatric surgery

Abstract: All POCT devices tested and operated by trained staff for hemoglobinometry showed reliable test results. They all allow for simple, fast, and precise bedside determination of hemoglobin concentration in the intraoperative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…42 reported a different analyzer (IPOC-1) having a lower mean Hb concentration (4.9 g/L). Spielmann et al, 138 Broderick et al., 43 and Zatloukal et al 106 analyzed venous blood by clinical laboratory blood gas analyzers compared with the reference in five comparisons. Broderick et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 reported a different analyzer (IPOC-1) having a lower mean Hb concentration (4.9 g/L). Spielmann et al, 138 Broderick et al., 43 and Zatloukal et al 106 analyzed venous blood by clinical laboratory blood gas analyzers compared with the reference in five comparisons. Broderick et al .…”
Section: Resultsmentioning
confidence: 99%
“…Spielmann et al found two different clinical blood gas analyzers (CBGA-1 and CBGA-2) to have a higher mean Hb concentration (5.8–8.0 g/L) and one analyzer (CBGA-3) to have a lower mean Hb concentration (0.5 g/L) compared with the reference. 138 When applying the mean concentration difference threshold of ±7% for the studies comparing the other portable photometric invasive POC analyzers or clinical laboratory blood gas analyzers with the reference, 11 studies including 17 comparisons 18,31,43,102,106,110,113,120,121,138 met the allowable degree of variation with one study exceeding the ±7% bias 42 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also compared the performance of HemoCue with different main laboratory analysers in ICU, during surgery or gastrointestinal bleeding episodes (Rippmann et al , ; Lardi et al , ; Gehring et al , ; Van de Louw et al , ; Mimoz et al , ; Lamhaut et al , ; Spielmann et al , ; Seguin et al , ). However, due to their small sample sizes and their extreme diversity in study design and methodologies, it is very difficult to evaluate the overall performance of HemoCue.…”
Section: Haemoglobin Poct In Hospital Settingsmentioning
confidence: 99%
“…However, due to their small sample sizes and their extreme diversity in study design and methodologies, it is very difficult to evaluate the overall performance of HemoCue. Some studies showed poor agreement in Hb levels (predominantly with capillary samples) between HemoCue and the mainstream laboratory analysers (Van de Louw et al , ; Seguin et al , ), whilst other studies reported more consistent results (McNulty et al , ; Gehring et al , ; Spielmann et al , ). Further, considering that the clinically acceptable Hb difference between different methods should be ≤10 g/l, it is evident that in some studies HemoCue has fallen short (Van de Louw et al , ; Rippmann et al , ; Lamhaut et al , ; Mimoz et al , ).…”
Section: Haemoglobin Poct In Hospital Settingsmentioning
confidence: 99%